2020
DOI: 10.31311/ji.v7i1.7576
|View full text |Cite
|
Sign up to set email alerts
|

Kajian Website Pendaftaran Peserta Pelatihan Pada Kemendag Dengan Pendekatan Technology Acceptance Model

Abstract: AbstrakPerdagangan dunia menunjukkan perkembangan dinamis terlebih dengan mulai diberlakukannya Free Trade Agreement. Hal ini perlu disikapi oleh para pelaku bisnis terutama eksportir dan calon eksportir, mengingat pasar internasional kini menuntut profesionalisme yang tinggi dan bukan sekedar transaksi. Dengan tuntutan tersebut, pelaku bisnis perlu memiliki keterampilan dan pengetahuan yang cukup untuk menangkap peluang serta memenuhi standar yang dikehendaki oleh pasar internasional. PPEI sebagai lembaga pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…TAM includes aspects of perceived ease of use, perceived usefulness, attitude toward attitude, behavioral intention, and actual usage. 17,[21][22][23][24][25][26][27][28] Some previous studies have also used TAM to describe the perception of user acceptance of an information system or technology that has been designed. Some previous studies such as Rahimi's research (2018) which used the Technology Acceptance Model (TAM) approach to analyze the acceptance of the use of health information systems 23 Jeffrey Campbell (2017) analyzed the use of TAM as a proposed acceptance of Mobile Health Intervention technology 29 Then in Bagot's study (2019) which used TAM to analyze user acceptance of acute stroke telemedicine services with the results obtained that from the aspect of perceived benefits, it was found that there were clinical improvements and patient care.…”
Section: Discussionmentioning
confidence: 99%
“…TAM includes aspects of perceived ease of use, perceived usefulness, attitude toward attitude, behavioral intention, and actual usage. 17,[21][22][23][24][25][26][27][28] Some previous studies have also used TAM to describe the perception of user acceptance of an information system or technology that has been designed. Some previous studies such as Rahimi's research (2018) which used the Technology Acceptance Model (TAM) approach to analyze the acceptance of the use of health information systems 23 Jeffrey Campbell (2017) analyzed the use of TAM as a proposed acceptance of Mobile Health Intervention technology 29 Then in Bagot's study (2019) which used TAM to analyze user acceptance of acute stroke telemedicine services with the results obtained that from the aspect of perceived benefits, it was found that there were clinical improvements and patient care.…”
Section: Discussionmentioning
confidence: 99%